2003
DOI: 10.1017/s0967199403002442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating human sperm DNA integrity: relationship between 8-hydroxydeoxyguanosine quantification and the sperm chromatin structure assay

Abstract: In our work, we have used 8-hydroxy-deoxyguanosine (8-OH-dG), one of the major oxidative products of sperm DNA, in a population of patients consulting for infertility. We found an inverse relationship between sperm concentration and the log of the ratio of 8-OH-dG to dG (P < 0.01). On the same patients' sperm samples, the sperm chromatin structure assay (SCSA) was performed. An inverse relationship was observed between the DNA fragmentation index and sperm concentration (P < 0.001). There was also a positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 21 publications
(32 reference statements)
0
37
0
2
Order By: Relevance
“…DNA fragmentation in mature male germ cell is usually caused by external factors such as reactive oxygen species (ROS), rather than cell's own programmed death [24]. Study has proven that DNA fragmentation measured by the SCSA originates (a part) from oxidative products (8-hydroxy-deoxyguanosine) [32]. It is therefore necessary to evaluate sperm DFI and the origin of increased DFI, so that a couple can be provided appropriate therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation in mature male germ cell is usually caused by external factors such as reactive oxygen species (ROS), rather than cell's own programmed death [24]. Study has proven that DNA fragmentation measured by the SCSA originates (a part) from oxidative products (8-hydroxy-deoxyguanosine) [32]. It is therefore necessary to evaluate sperm DFI and the origin of increased DFI, so that a couple can be provided appropriate therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of reactive oxygen species (ROS) and ROS-related DNA oxidative products, such as 8-hydroxy-deoxyguanosine (8-OHdG) have also been associated with sperm DNA fragmentation (17,25). It has been shown that as sperm concentration decreases, DNA fragmentation index and 8-OH-dG increase, suggesting that ROS and the relevant products may have a major impact on sperm DNA integrity (25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that as sperm concentration decreases, DNA fragmentation index and 8-OH-dG increase, suggesting that ROS and the relevant products may have a major impact on sperm DNA integrity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA damage can arise by different mechanisms, among which it is believed that the excess production of ROS plays a major role [Aitken et al 1998;Henkel et al 2005;Oger et al 2003;Saleh et al 2002a;Wang et al 2003]. Reactive oxygen species can originate from endogenous sources such as leukocytes and immature spermatozoa [Aitken and West 1990;Kessopoulou et al 1992;Shekarriz et al 1995], as well as, exogenous sources such as industrial compounds, smoking, and alcohol [Acharya et al 2003;Agarwal and Saleh 2002;Kasahara et al 2002;Koch et al 2004;Kothari et al 2010;Saleh et al 2002b].…”
Section: Introductionmentioning
confidence: 99%